Assessment of Sudanese sunflower hybrids for yield, yield components and stability - Mohamed, Mohamed; Elzein, Ibrahim; Ahmed, Mohamed; Ibrahim, Abu Elhassan (Gezira Journal of Agricultural Science, 2014)
Development of local sunflower hybrids with superior yields and stable across different environments is the main objective in our breeding program. For this purpose, ten local Sudanese sunflower hybrids designated as SFH32, SFH36, SFH37, SFH310, SFH313, SFH314, SFH341, SFH345, SFH302, and SFH325 were evaluated against Hysun-33 for yield potential and its components at Sennar, Wad Medani, Rahad, New Halfa and Suki. The experiment over all irrigated environments was laid out in RCBD with three replicates during the winter season of 2008. There was considerable variation for yield and its components among hybrids and locations. Genotype-environment interactions through different parameters and the performance of six traits of hybrids were studied. The six traits were plant height (cm), number of seeds per head, percentage of empty seeds,    100-seed weight (g),seed yield (kg ha -1 ) and oil yield (kg ha -1 ).Significant differences were observed for hybrids (G), locations (E) and G xE interaction for these six traits. Stability analysis after Eberhart and Russell’s model suggested that the hybrids used in this study were all, more or less, responsive to environmental changes. Most of the hybrids performed better in E4 (New Halfa). Stability analysis identified SFH37 and SFH310 as stable hybrids for plant height, SFH345 and SFH302 were identified as stable for number of seeds per head, whereas, Hysun-33, SFH310 and SFH341 were found stable for low percentage of empty seeds and heavy seed weight, respectively. Three hybrids; SFH310, SFH313 and SFH341 performed better than Hysun-33 and other hybrids across five environments and were considered as most stable hybrids for seed and oil yields. In contrast, hybrids such as SFH32 and SFH37 with regression coefficients greater than one were regarded as sensitive to environmental changes for seed and oil yields. The hybrid SFH310 was identified as stable hybrid for various yield components. The three promising local hybrids were released in June 2009 for commercial production and the local seed production of the hybrid SFH310 (Bohooth-1) was adopted by some seed producers in the country. تطوير هجن محلية من محصول زهرة الشمس ذات إنتاجية عالية وثابته  فى مختلف البيئات ، يعتبر من أهم أهداف برنامج التربية. أجريت هذه التجربة للتقييم عشرة هجن محلية بالرموز SFH32، SFH36 ، SFH37، SFH310، SFH313، SFH314، SFH341، SFH345، SFH3302، و25SFH3 واختبارها مع الشاهد Hysun-33 فى خمسة بيئات مروية هى سنار ، واد مدني، الرهد، حلفا الجديدة، والسوكي لمعرفة مقدرتها الإنتاجية الكامنة. أستخدم تصميم القطاعات العشوائية الكاملة بثلاثة مكررات لتنفيذ التجربة فى كل موقع خلال الموسم الشتوي 2008/2009. أوضحت النتائج وجود فروقات كبيرة فى الإنتاجية و مكوناتها بين الهجن والمواقع. كما أوضح تفاعل الطرز الوراثية مع البيئة ((genotype x environment interactions وجود فروقات معنوية عالية لسته صفات تمت دراستها وهى أطوال النباتات (سنتمترات) وعدد البذور بالقرص والنسبة المئوية للبذور الفارغة ووزن المائة بذرة (جرامات) وإنتاجية البذور(كيلوجرامات/هكتار) وإنتاجية الزيت (كيلوجرامات/هكتار).أوضح تحليل ثبات الإنتاجية  stability analysis بإســـــــتخدام نموذج Eberhart and Russell’s model بان جميع الهجن لها استجابات متباينة مع المتغيرات البيئية فى المواقع الخمسة وكان أفضل الأداء فى حلفا الجديدة (.(E4 كما أوضح التحليل بان الهجينين SFH37  و SFH310 هما من الهجن المستقرة و الثابتة الأداء لصفة أطوال النباتات و الهجينين SFH345  و SFH302 لصفة عدد البذور بالقرص ، بينما الهجن Hysun-33  ، SFH310، وSFH341 لصفتي النسبة المنخفضة من البذور الفارغة والوزن المرتفع للمائة بذرة علي التوالي. أوضحت الدراسة ان ثلاثة هجن محلية  (SFH310، SFH313 و SFH341) وخاصة الهجين SFH310 ، لها مقدرة إنتاجية عالية من البذور والزيت وثبات الإنتاجية فى البيئات الخمسة مقارنة مع الشاهد Hysun-33 وباقي الهجن ، بينما هجن اخرى مثل الهجينين SFH32  وSFH37  تعتبر حساسة للتغيرات البيئة فى إنتاجيتها من البذور والزيت. تم التعرف على الهجين SFH310 بأنه أكثر ثباتاً للإنتاجية ومكوناتها. الهجن السودانية الثلاثة الواعدة تمت إجازتها في يونيو 2009 للإنتاج التجاري والأنتاج المحلي لبذور الهجين SFH310 (بحوث-1= Bohooth-1) تم تبنيه من بعض منتجي البذور فى السودان.